Composite for carbon dioxide separation

By using meltblown non-woven fabric as a support material and water-soluble polymer amine compound as a carbon dioxide transport carrier in the carbon dioxide separation membrane, the problem of difficult to balance the selectivity and flux of the carbon dioxide separation membrane in the prior art is solved, and the physical strength and separation performance of the membrane are improved.

JP2025047771APending Publication Date: 2025-04-03MITSUI CHEMICALS INC +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023156470
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

The existing hydrocarbon separation membranes are difficult to balance the selectivity and flux of carbon dioxide, and the physical strength is insufficient, which limits its popularity in practical applications.

Method used

A carbon dioxide separation composite film with meltblown non-woven fabric as the support material is used, which comprises a carbon dioxide separation functional layer, in which a carbon dioxide transport carrier such as water-soluble polymers and amine compounds are used.

Benefits of technology

The carbon dioxide selectivity and flux are achieved, and the physical strength and gas separation performance of the carbon dioxide separation membrane are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047771000011
    Figure 2025047771000011
  • Figure 2025047771000001
    Figure 2025047771000001
  • Figure 2025047771000002
    Figure 2025047771000002
Patent Text Reader

Abstract

To provide a composite for carbon dioxide separation that maintains carbon dioxide permeability and offers superior selectivity for carbon dioxide.SOLUTION: A composite for carbon dioxide separation comprises a carbon dioxide separation functional layer and a support, wherein the support comprises a melt-blown nonwoven fabric composed of fibers having an average fiber diameter of less than 1.5 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composite for carbon dioxide separation. [Background technology]

[0002] Global warming caused by the increase in carbon dioxide emissions has become a problem, and active efforts are being made to reduce emissions. In recent years, technology to capture carbon dioxide contained in exhaust gases emitted from large-scale carbon dioxide emission sources such as thermal power plants, steelworks blast furnaces, and chemical plants has been attracting attention.

[0003] Conventionally, chemical absorption and physical adsorption methods have been used as carbon dioxide capture technologies, but the costs of separation and capture are high, making their introduction difficult.

[0004] In recent years, therefore, attention has been focused on membrane separation methods, which have low separation and recovery costs. Membrane separation methods use the pressure difference between the inside and outside of a membrane as a driving force, and are a method of selectively separating carbon dioxide by passing it through a composite material that combines a separation functional layer with a support that physically reinforces the separation functional layer.

[0005] To date, research and development of separation functional layers has been actively conducted in order to separate carbon dioxide more efficiently. However, it is known that there is a trade-off between the carbon dioxide permeation rate and selectivity, and it has been difficult to improve both performances at the same time (for example, see Non-Patent Document 1). Therefore, there have been no examples of membrane separation methods being put into practical use, with only Polaris (registered trademark) from MTR in the United States having reached the pilot test level (for example, see Non-Patent Document 2).

[0006] In addition, the separation functional layer having the function of separating carbon dioxide needs to be a thin film in order to ensure a sufficient carbon dioxide permeation rate, and does not have the physical strength to be used alone. Therefore, the separation functional layer is used as a composite combined with a support, which is a porous substrate that has low gas transport resistance and can ensure physical strength.

[0007] For example, Patent Document 1 describes a composite obtained by applying a gel layer, in which an epoxy crosslinking agent or the like is added to an aqueous polyvinyl alcohol-polyacrylate copolymer solution, to a porous membrane soaked in a radical polymerization initiator, and then carrying out UV irradiation and annealing treatment.

[0008] For example, Patent Document 2 describes a polymer membrane in which a gel layer formed by adding N-(2-aminoethyl)ethanolamine to a polyvinyl alcohol gel membrane is supported on a porous membrane. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2013-027806 A [Patent Document 2] JP 2018-144022 A [Non-patent literature]

[0010] [Non-Patent Document 1] Journal of Membrane Science, 320(2008), 390-400 [Non-Patent Document 2] Journal of Membrane Science, 359(2010), 126-139 Summary of the Invention [Problem to be solved by the invention]

[0011] However, although the membranes described in Patent Documents 1 and 2 focus on the separation functional layer, their carbon dioxide selectivity is insufficient and they are not suitable for practical use.

[0012] The problem to be solved by the present disclosure is to provide a composite for carbon dioxide separation that has excellent carbon dioxide selectivity while maintaining the carbon dioxide permeation rate. [Means for solving the problem]

[0013] Specific means for solving the problems include the following aspects. <1> The composite for carbon dioxide separation includes a carbon dioxide separation functional layer and a support, the support including a meltblown nonwoven fabric made of fibers having an average fiber diameter of less than 1.5 μm. <2> The average fiber diameter of the fibers is 0.3 μm to 1.2 μm. <1> The carbon dioxide separation composite is as described above. <3> The average pore size of the meltblown nonwoven fabric is less than 6.0 μm. <1> or <2> The carbon dioxide separation composite is as described above. <4> The fiber is made of a resin composition containing a propylene homopolymer. <1> ~ <3> The carbon dioxide separation composite according to any one of the above items.

[0014] <5> The carbon dioxide separation functional layer satisfies either (A) or (B) below. <1> ~ <4> The carbon dioxide separation composite according to any one of the above items. (A) A water-soluble polymer and at least one amine compound selected from the group consisting of an amine compound represented by the following formula (1), an amine compound represented by the following formula (2), and a polyethylene polyamine compound. (B) 4-methyl-1-pentene polymer

[0015] [ka]

[0016] In formula (1), R1, R3 and R3 each independently represent a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a hydroxyethyl group.

[0017] [ka]

[0018] In formula (2), R1, R3 and R4 each independently represent a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0019] <6> The carbon dioxide separation functional layer satisfies the following (A): <5> The carbon dioxide separation composite is as described above. (A) a water-soluble polymer comprising polyvinyl alcohol and at least one amine compound selected from the group consisting of the amine compound represented by the formula (1), the amine compound represented by the formula (2), and a polyethylene polyamine compound; <7> The weight average molecular weight of the water-soluble polymer is 2,000 to 1,000,000. <5> or <6> The carbon dioxide separation composite is as described above. Effect of the Invention

[0020] According to the present disclosure, there is provided a composite for carbon dioxide separation that has excellent carbon dioxide selectivity while maintaining a carbon dioxide permeation rate. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic diagram of an apparatus for conducting a gas separation test on a mixed gas containing carbon dioxide and a coexisting gas. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The composite for carbon dioxide separation according to the present disclosure will be described in detail below. The present disclosure is not limited to the following embodiments. The following embodiments may be modified as appropriate within the scope of the object of the present disclosure.

[0023] In this specification, a numerical range indicated using "~" indicates a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in this specification, the upper limit or lower limit described in a certain numerical range may be replaced with the upper limit or lower limit of another numerical range described in a certain numerical range. In addition, in the numerical ranges described in this specification, the upper limit or lower limit described in a certain numerical range may be replaced with a value shown in the examples.

[0024] In this specification, the amount of each component in a composition means, when a plurality of substances corresponding to each component are present in the composition, the total amount of the corresponding substances present in the composition, unless otherwise specified.

[0025] In this specification, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps as long as a desired purpose is achieved.

[0026] In this specification, "wt %" and "mass %" are synonymous, and "parts by mass" and "parts by weight" are synonymous.

[0027] The carbon dioxide separation composite of the present disclosure (hereinafter also simply referred to as the "composite") includes a carbon dioxide separation functional layer (hereinafter also simply referred to as the "separation functional layer") and a support, and may have other layers as necessary. The support of the composite of the present disclosure includes a meltblown nonwoven fabric made of fibers having an average fiber diameter of less than 1.5 μm. The composite having the above structure exhibits excellent carbon dioxide selectivity while maintaining the carbon dioxide permeation rate. The reason why the composite of the present disclosure maintains the carbon dioxide permeation rate and exhibits excellent carbon dioxide selectivity is presumed to be as follows. That is, by using a meltblown nonwoven fabric as the nonwoven fabric constituting the support, a dense structure with many voids made of fine fibers is obtained compared to conventional porous supports, resulting in high breathability and a good carbon dioxide permeation rate. In addition, since the average fiber diameter of the meltblown nonwoven fabric is less than a certain value, it is easy to adjust the average pore size, so that the selective permeation performance of gas molecules is enhanced and carbon dioxide selectivity is improved. This synergistically enhances the effect of the gas separation layer that selectively permeates carbon dioxide gas, improving carbon dioxide selectivity while maintaining the carbon dioxide permeation rate of the composite membrane.

[0028] [Carbon dioxide separation layer] The composite of the present disclosure includes at least one separation functional layer that separates carbon dioxide. By including the separation functional layer, carbon dioxide can be selectively separated. In the composite of the present disclosure, only one separation functional layer may be provided, but two or more separation functional layers may also be provided.

[0029] The separating functional layer of the present disclosure is not particularly limited as long as it is selectively permeable to carbon dioxide. Examples of the separation functional layer include layers using polymers such as water-soluble polymers, olefin polymers, polyimide compounds, and siloxane polymers, and carbon dioxide transport carriers such as amine compounds having high affinity with carbon dioxide. These compounds may be contained in the separation functional layer alone or in combination of two or more kinds.

[0030] (Water-soluble polymer) The water-soluble polymer plays a role in maintaining the membrane structure of the separation functional layer, retaining moisture and carbon dioxide carriers in the separation functional layer, and exerting good carbon dioxide selectivity. Examples of the water-soluble polymer include polyvinyl alcohol compounds, polyacrylic acid compounds, polyethylene glycol compounds, polyvinylpyrrolidone compounds, polysaccharides, and copolymers thereof. Among these, from the viewpoints of water absorbency, film-forming properties, strength, etc., polyvinyl alcohol, polyacrylic acid, pullulan, and dextran are preferred, and polyvinyl alcohol is more preferred.

[0031] The separation functional layer preferably contains polyvinyl alcohol. By containing polyvinyl alcohol, the layer structure of the separation functional layer is easily maintained. It is also preferable that the separation functional layer contains polyvinyl alcohol and an amine compound (carbon dioxide transport carrier).

[0032] The polyvinyl alcohol is not particularly limited as long as it dissolves in water and forms a membrane when dried, but it is preferable that it has high water absorption. By having water absorption, it is possible to improve carbon dioxide selectivity. The polyvinyl alcohol is preferably obtained by alkaline hydrolysis (saponification) of polyvinyl acetate. Examples of polyvinyl alcohol include fully saponified polyvinyl alcohol in which all carboxyl groups have been replaced with hydroxyl groups, and polyvinyl alcohol in which some of the carboxyl groups have been replaced with hydroxyl groups. Partially saponified polyvinyl alcohol, etc. These may be used alone or in combination of two or more.

[0033] Examples of commercially available polyvinyl alcohol products include polyvinyl alcohol manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., the Kuraray Poval series manufactured by Kuraray Co., Ltd., the Gohsenex (registered trademark) series manufactured by Mitsubishi Chemical Corporation, and the Poval series manufactured by Nippon Vacuum Acetate & Poval Co., Ltd.

[0034] The weight-average molecular weight of the water-soluble polymer (preferably polyvinyl alcohol) is preferably 2,000 to 1,000,000. If the weight-average molecular weight is 2,000 or more, the film strength after drying is easily maintained. Also, if the weight-average molecular weight is 1,000,000 or less, the viscosity is not too high and the film thickness uniformity is improved.

[0035] The content of the water-soluble polymer (preferably polyvinyl alcohol) is not particularly limited, and is preferably 2% to 80% by mass, more preferably 30% to 70% by mass, and even more preferably 40% to 60% by mass, based on the entire separation functional layer. If the content of the water-soluble polymer is within the above range, the coating property of the coating solution when forming the separation functional layer by coating is good, and the durability of the separation functional layer can be imparted.

[0036] The water-soluble polymer may be produced using a raw material derived from biomass.

[0037] (Amine compounds) The amine compound plays a role in adsorbing and desorbing carbon dioxide in the separation functional layer. Examples of the amine compound include an amine compound represented by the following formula (1), an amine compound represented by the following formula (2), a polyethylene polyamine compound, and an alkanolamine.

[0038] From the viewpoint of carbon dioxide adsorption / desorption performance, the amine compound is preferably at least one selected from the group consisting of amine compounds represented by the following formula (1), amine compounds represented by the following formula (2), and polyethylene polyamine compounds, and more preferably at least one selected from the group consisting of amine compounds represented by the following formula (1) and amine compounds represented by the following formula (2).

[0039] -Amine compound represented by formula (1)-

[0040] [ka]

[0041] In formula (1), R1, R3 and R3 each independently represent a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a hydroxyethyl group. In formula (1), examples of the alkyl group having 1 to 4 carbon atoms in R1, R3, and R3 include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, etc. Among these, it is preferable that R1, R3, and R3 are each independently a hydrogen atom, a methyl group, or an ethyl group, and it is more preferable that R1, R3, and R3 simultaneously represent the same group and are a hydrogen atom, a methyl group, or an ethyl group.

[0042] Among the compounds represented by formula (1), specific examples of compounds in which R1, R3, and R3 simultaneously represent the same group and are a hydrogen atom, a methyl group, or an ethyl group include N-(2-aminoethyl)ethanolamine, 2-[[2-(dimethylamino)ethyl]methylamino]ethanol, and N-[2-(diethylamino)ethyl]ethanolamine.

[0043] -Amine compound represented by formula (2)-

[0044] [ka]

[0045] In formula (2), R1, R3 and R4 each independently represent a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0046] In the formula (2), examples of the alkyl group having 1 to 4 carbon atoms in R1, R3 and R3 include a methyl group, an ethyl group, a propyl group, an isopropyl group, and a butyl group.

[0047] Examples of the compound represented by formula (2) include N-(1,2-dihydroxy-n-propyl)piperazine, N-[(1-hydroxymethyl, 2-hydroxy)-n-propyl]piperazine, N-[(1-hydroxy, 2-hydroxymethyl)-n-propyl]piperazine, N-(1,2-dihydroxy-n-propyl)-N'-methyl-piperazine, N-[1,2-bis(hydroxymethyl)-n-propyl]piperazine, and N-[1,2-bis(hydroxymethyl)-n-propyl]-N'-methyl-piperazine.

[0048] Among the above, preferred amine compounds represented by formula (1) or formula (2) are N-(2-aminoethyl)ethanolamine, N-(1,2-dihydroxy-n-propyl)piperazine, and the like.

[0049] -Polyethylene polyamine compounds- Examples of polyethyleneamine compounds include diethylenetriamine (DETA), triethylenetetramine (TETA), tetraethylenepentamine (TEPA), and pentaethylenehexamine (PEHA).

[0050] "TETA" refers to a compound in which four amino groups are connected in a linear or branched manner via an ethylene chain, and in the present disclosure, also includes compounds having four amino groups and a piperazine ring structure. Specific examples of TETA include 1,4,7,10-tetraazadecane, N,N-bis(2-aminoethyl)-1,2-ethanediamine, 1-[2-[(2-aminoethyl)amino]ethyl]-piperazine, and 1,4-bis(2-aminoethyl)-piperazine.

[0051] "TEPA" refers to a compound in which five amino groups are connected in a linear or branched manner via an ethylene chain, and in the present disclosure, it also includes compounds having five amino groups and a piperazine ring structure. Specific examples of TEPA include 1,4,7,10,13-pentaazatridecane, N,N,N'-tris(2-aminoethyl)-1,2-ethanediamine, 1-[2-[2-[2-[(2-aminoethyl)amino]ethyl]amino]ethyl]-piperazine, 1-[2-[bis(2-aminoethyl)amino]ethyl]-piperazine, and bis[2-(1-piperazinyl)ethyl]amine.

[0052] "PEHA" refers to a compound in which six amino groups are linked in a linear or branched manner via an ethylene chain, and in the present disclosure also includes compounds that have six amino groups and also have a piperazine ring structure. Specific examples of PEHA include 1,4,7,10,13,16-hexaazahexadecane, N,N,N',N'-tetrakis(2-aminoethyl)-1,2-ethanediamine, N,N-bis(2-aminoethyl)-N'-[2-[(2-aminoethyl)amino]ethyl]-1,2-ethanediamine, 1-[2-[2-[2-[2-[2-[(2-aminoethyl)amino]ethyl]amino]ethyl]amino]ethyl]-piperazine, 1-[2-[2-[2-[bis(2-aminoethyl)amino]ethyl]amino]ethyl]piperazine, and N,N'-bis[2-(1-piperazinyl)ethyl]-1,2-ethanediamine, and the like.

[0053] The polyethylene polyamine compound may be one or more selected from the group consisting of diethylenetriamine (DETA), 1,4,7,10-tetraazadecane, N,N-bis(2-aminoethyl)-1,2-ethanediamine, 1-[2-[(2-aminoethyl)amino]ethyl]-piperazine, and 1,4-bis(2-aminoethyl)-piperazine. and one or more of tetraethylenepentamine (TEPA), 1,4,7,10,13,16-hexaazahexadecane, N,N,N',N'-tetrakis(2-azaethyl)amine selected from the group consisting of triethylenetetramine (TETA), 1,4,7,10,13-pentaazatridecane, N,N,N'-tris(2-aminoethyl)-1,2-ethanediamine, 1-[2-[2-[2-[(2-aminoethyl)amino]ethyl]amino]ethyl]-piperazine, 1-[2-[bis(2-aminoethyl)amino]ethyl]-piperazine, and bis[2-(1-piperazinyl)ethyl]amine. and N,N-bis(2-aminoethyl)-N'-[2-[(2-aminoethyl)amino]ethyl]-1,2-ethanediamine, 1-[2-[2-[2-[2-[2-[2-[(2-aminoethyl)amino]ethyl]amino]ethyl]-piperazine, 1-[2-[2-[2-[2-[bis(2-aminoethyl)amino]ethyl]amino]ethyl]piperazine, and N,N'-bis[2-(1-piperazinyl)ethyl]-1,2-ethanediamine are preferred.

[0054] Examples of alkanolamines include various water-soluble alkanolamines such as monoethanolamine, diethanolamine, triethanolamine, monopropanolamine, dipropanolamine, and tripropanolamine.

[0055] The amine compound contained in the separation functional layer is not particularly limited, and may be a commercially available product or may be one synthesized by a known method.

[0056] The purity of the amine compound is not particularly limited, but is preferably 95% or more, and particularly preferably 99% or more. If the purity is less than 95%, the amount of carbon dioxide absorbed may decrease.

[0057] The content of the amine compound contained in the separation functional layer is not particularly limited, and is preferably 2% by mass to 80% by mass, more preferably 30% by mass to 70% by mass, and even more preferably 40% by mass to 60% by mass, based on the entire separation functional layer. The amine compound may be produced using a raw material derived from biomass.

[0058] (Olefin Polymer) Next, the olefin polymer will be described. Specific examples of olefin polymers include homopolymers or copolymers of α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, and 4-methyl-1-hexene. Among these, 4-methyl-1-pentene polymers are more preferred from the viewpoint of excellent carbon dioxide permeation rate.

[0059] The separating functional layer in the present disclosure preferably contains a 4-methyl-1-pentene polymer, which improves the carbon dioxide permeation rate.

[0060] The 4-methyl-1-pentene polymer is a polymer containing 4-methyl-1-pentene as a main component, and is not particularly limited as long as it is a polymer having a structural unit derived from 4-methyl-1-pentene. The 4-methyl-1-pentene polymer may be a 4-methyl-1-pentene homopolymer or a 4-methyl-1-pentene copolymer. The "main component" refers to the component that is contained in the largest amount (highest mass %) among the components that constitute the polymer.

[0061] The 4-methyl-1-pentene polymer preferably satisfies the following requirements (a) and (b).

[0062] [Requirement (a)] The density of 4-methyl-1-pentene polymer is 0.80 kg / m3 ~0.90kg / m 3 is preferable, and 0.80 kg / m 3 ~0.88kg / m 3 More preferably, 0.80 kg / m 3 ~0.85kg / m 3 When the density of the 4-methyl-1-pentene polymer is within this range, the separation functional layer can maintain its carbon dioxide permeability while ensuring its mechanical strength. The density of the 4-methyl-1-pentene polymer is a value measured in accordance with JIS K7112 (density gradient tube method).

[0063] [Requirement (b)] The melting point (Tm) of the 4-methyl-1-pentene polymer is preferably from 200° C. to 260° C., more preferably from 200° C. to 250° C., and even more preferably from 210° C. to 250° C. When the melting point is within the above range, the separating functional layer has excellent heat resistance.

[0064] The melting point (Tm) is measured by differential scanning calorimetry (DSC) using a DSC measuring device (for example, DSC220C DSC measuring device manufactured by Seiko Instruments Inc.) in accordance with ASTM D3418. The melting point is determined by obtaining an exothermic / endothermic curve and taking the temperature at the maximum melting peak position during heating. Specifically, the measurement is performed as follows.

[0065] Approximately 5 mg of the sample is placed in a measurement aluminum pan, heated from 20°C to 280°C at a heating rate of 10°C / min, held at 280°C for 5 minutes, cooled to 20°C at a cooling rate of 10°C / min, held at 20°C for 5 minutes, and then heated again from 20°C to 280°C at a heating rate of 10°C / min. The melting peak that appears during the second heating is taken as the melting point (Tm). If multiple peaks are detected, the peak with the highest temperature is taken as the melting point (Tm). When a 4-methyl-1-pentene polymer is obtained in a two-stage polymerization process of polymerization process 1 and polymerization process 2, the melting point (Tm) of the polymer (component 2) produced in polymerization process 2 is determined by analyzing the polymer produced in polymerization process 1 and the final polymer.

[0066] The 4-methyl-1-pentene polymer is not particularly limited as long as it satisfies the above requirements (a) and (b), but it is preferable that the polymer further satisfies the following requirements (c) and (d).

[0067] [Requirement (c)] The 4-methyl-1-pentene polymer has a content of the structural unit (P) derived from 4-methyl-1-pentene of usually 80 mol% or more and 100 mol% or less, more preferably 90 mol% or more and 100 mol% or less, and even more preferably 95 mol% or more and 100 mol% or less, and has a total content of the structural unit (AQ) derived from at least one olefin selected from α-olefins having 2 to 20 carbon atoms other than 4-methyl-1-pentene of 0 mol% or more and 20 mol% or less, preferably 0 mol% or more and 10 mol% or less, and even more preferably 0 mol% or more and 5 mol% or less (however, the total content of the structural unit (P) and the structural unit (AQ) is 100 mol%).

[0068] When the content of the structural unit (P) in the 4-methyl-1-pentene polymer is 80 mol % or more, the uniformity of the film formed into a separating functional layer is increased.

[0069] Specific examples of α-olefins having 2 to 20 carbon atoms other than 4-methyl-1-pentene that form the structural unit (AQ) include ethylene, propylene, 1-butene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene, etc. Specific examples of α-olefins that form the structural unit (AQ) are more preferably at least one selected from olefins having 8 to 18 carbon atoms, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-heptadecene, and 1-octadecene, from the viewpoint of realizing a higher carbon dioxide permeation rate by increasing the free volume between polymer chains.

[0070] The 4-methyl-1-pentene polymer may contain other structural units than the structural unit (P) derived from 4-methyl-1-pentene and the structural unit (AQ) derived from at least one olefin selected from α-olefins other than 4-methyl-1-pentene, within a range that does not impair the effects of the present disclosure. The content of the other structural units is, for example, 0 to 10 mol% (however, the total content of the structural unit (P) and the structural unit (AQ) is 100 mol%).

[0071] Specific examples of monomers that form other structural units include cyclic olefins, aromatic vinyl compounds, conjugated dienes, non-conjugated polyenes, functional vinyl compounds, hydroxyl group-containing olefins, and halogenated olefins.

[0072] Specific examples of the cyclic olefin, aromatic vinyl compound, conjugated diene, non-conjugated polyene, functional vinyl compound, hydroxyl group-containing olefin, and halogenated olefin include the compounds described in paragraphs 0034 to 0041 of JP-A No. 2013-169685.

[0073] As the monomer forming the other structural unit, vinylcyclohexane and styrene are particularly preferable. When the 4-methyl-1-pentene polymer has the other structural unit, the other structural unit may be contained in only one type or in two or more types. The content (mol%) of each structural unit in the polymer (A) is 13 It is measured by C-NMR.

[0074] [Requirement (d)] The 4-methyl-1-pentene polymer usually has a melt flow rate (MFR) of 0.01 g / 10 min to 500 g / 10 min under a load of 5 kg at 260° C., measured in accordance with ASTM D1238. This melt flow rate is preferably 5 g / 10 min to 300 g / 10 min, more preferably 10 g / 10 min to 200 g / 10 min. If the MFR is within this range, it is preferable from the viewpoint of fluidity during molding of the separation functional layer. In addition, since there is a small amount of low molecular weight substances, the resulting separation functional layer is less sticky. The 4-methyl-1-pentene polymer may be a graft-modified polymer obtained by graft-modifying a polymer with a polar monomer, so long as the requirements (a) to (d) are satisfied.

[0075] The method for producing the 4-methyl-1-pentene polymer is not particularly limited, and the polymer may be produced by polymerizing an olefin compound containing 4-methyl-1-pentene, or by pyrolyzing a high molecular weight 4-methyl-1-pentene polymer. The 4-methyl-1-pentene polymer may be purified by a method such as solvent fractionation for fractionation based on the difference in solubility in a solvent, or molecular distillation for fractionation based on the difference in boiling point.

[0076] As a method for producing a 4-methyl-1-pentene polymer, for example, the methods described in WO 2001 / 27124, WO 2014 / 050817, etc. can be adopted. In addition, a conventionally known polymerization catalyst can be used.

[0077] When the 4-methyl-1-pentene polymer is a graft modified product, the graft modified product can be produced by grafting a polar monomer onto the 4-methyl-1-pentene polymer to be modified. The modification method is not particularly limited, and for example, the polar monomer may be graft polymerized onto the modified product, or the modified product may be reacted with the polar monomer using an extruder or the like to produce the graft modified product.

[0078] Specific examples of polar monomers used for graft modification include hydroxyl group-containing ethylenically unsaturated compounds, amino group-containing ethylenically unsaturated compounds, epoxy group-containing ethylenically unsaturated compounds, aromatic vinyl compounds, unsaturated carboxylic acids or derivatives thereof, vinyl ester compounds, vinyl chloride, and carbodiimide compounds. In particular, unsaturated carboxylic acids or derivatives thereof are preferred. Examples of unsaturated carboxylic acids or derivatives thereof include unsaturated compounds having one or more carboxylic acid groups, esters of compounds having carboxylic acid groups and alkyl alcohols, and unsaturated compounds having one or more carboxylic anhydride groups. Examples of unsaturated groups include vinyl groups, vinylene groups, and unsaturated cyclic hydrocarbon groups. These polar monomers may be used alone or in combination of two or more.

[0079] When the separation functional layer contains a 4-methyl-1-pentene polymer, the separation functional layer may contain various additives such as weathering stabilizers, heat stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, slip prevention agents, antiblocking agents, antifogging agents, nucleating agents, lubricants, pigments, dyes, antioxidants, hydrochloric acid absorbers, inorganic or organic fillers, organic or inorganic foaming agents, crosslinking agents, crosslinking assistants, adhesives, softeners, and flame retardants, and polymers other than the 4-methyl-1-pentene polymer, within the range that does not impair the object of the present invention. The content of components other than the 4-methyl-1-pentene polymer is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the 4-methyl-1-pentene polymer.

[0080] When the separation functional layer contains a 4-methyl-1-pentene polymer, the separation functional layer may contain other polymers (hereinafter referred to as "other polymers") other than the 4-methyl-1-pentene polymer, within the scope that does not impair the objective of the present invention. Specific examples of other polymers include polyolefins, polyamides, polyesters, and vinyl aromatic polymers that do not fall under any of the 4-methyl-1-pentene polymers. Specific examples of polyolefins that do not fall under any of the 4-methyl-1-pentene polymers include polyethylene, polypropylene, poly-1-butene, ethylene-propylene copolymers, ethylene-1-butene copolymers, propylene-1-butene copolymers, ethylene-propylene-1-butene copolymers, ethylene-propylene-1-hexene copolymers, ethylene-propylene-1-octene copolymers, ethylene-1-butene-1-hexene copolymers, ethylene-1-butene-1-octene copolymers, ethylene-α-olefin-non-conjugated diene copolymers, and other various olefin polymers other than the 4-methyl-1-pentene polymers of the present disclosure; as well as halogen-containing polymers such as chlorinated polyethylene, polyvinyl chloride, and polyvinylidene chloride.

[0081] Specific examples of polyamides include polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 66, polyamide 610, polyamide 6T / 66 copolymer, polyamide 6T / 6I copolymer, polyamide 9T, and polyamide 10T. Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyarylate, and polyester elastomers. Specific examples of vinyl aromatic polymers include polystyrene, acrylonitrile-butadiene-styrene copolymers, acrylonitrile-styrene copolymers, and styrene elastomers. Other examples of polymers besides those mentioned above include vinyl alcohol copolymers, acrylic resins, thermoplastic polyurethanes, vinyl chloride resins, polycarbonates, fluorine-based resins, polyphenylene ethers, polyphenylene sulfides, polyimides, polysulfones, polyether sulfones, copolymer rubbers, and petroleum resins.

[0082] The content of the other polymers is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, based on the total mass of the 4-methyl-1-pentene polymer. The olefin polymer may be produced using a raw material derived from biomass.

[0083] (Carbon dioxide transport carrier) The carbon dioxide transport carrier may be any one that has affinity for carbon dioxide and is water-soluble, and may be appropriately selected from known ones. Examples of carbon dioxide transport carriers include water-soluble inorganic and organic substances that have basicity as substances that have affinity for carbon dioxide. For example, inorganic substances selected from the group consisting of alkali metal carbonates, alkali metal bicarbonates, and alkali metal hydroxides; aqueous solutions containing alkali metal carbonates, alkali metal bicarbonates, and alkali metal hydroxides to which multidentate ligands that form complexes with alkali metal ions have been added; ammonia; ammonium salts; various linear or cyclic amines; amine salts; and the like, as well as water-soluble derivatives thereof. The carbon dioxide transport carrier may be used alone or in combination of two or more kinds.

[0084] Examples of the alkali metal carbonate include lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, and cesium carbonate. Examples of the alkali metal bicarbonate include lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, rubidium hydrogen carbonate, and cesium hydrogen carbonate. Examples of the alkali metal hydroxide include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide. Among these, compounds containing potassium, rubidium, or cesium are preferred from the viewpoint of good affinity with carbon dioxide. In addition, since it is advantageous for the carbon dioxide transport carrier to be retained in the carbon dioxide separation functional layer for a long period of time, it is also preferable to use an inorganic substance selected from the group consisting of alkali metal carbonates, alkali metal bicarbonates, and alkali metal hydroxides in combination with an amine-containing compound that is difficult to evaporate (such as amino acids or betaines).

[0085] The above-mentioned alkanolamines can also function as carbon dioxide transport carriers. The carbon dioxide transport carrier is not limited to those mentioned above, and any alkali metal salt of an organic acid can be used as long as it has affinity for carbon dioxide and is water-soluble.

[0086] The polydentate ligand that forms a complex with an alkali metal ion can be appropriately selected from conventionally known ligands, and examples thereof include 12-crown-4, 15-crown-5, 18-crown-6, benzo-12-crown-4, benzo-15-crown-5, benzo-18-crown-6, dibenzo-12-crown-4, dibenzo-15-crown-5, dibenzo-18-crown-6, dicyclohexyl-12-crown-4, dicyclohexyl-15-crown-5, dicyclohexyl-12-crown-4, dicyclohexyl-15-crown-5, dicyclohexyl-18-crown-6, dicyclohexyl-12-crown-4, dicyclohexyl-15-crown-5, dicyclohexyl-18-crown-6, dicyclohexyl-18-crown-4, dicyclohexyl-18 ... Cyclic polyethers such as cyclohexyl-18-crown-6, n-octyl-12-crown-4, n-octyl-15-crown-5, and n-octyl-18-crown-6; cyclic polyetheramines such as cryptand [2.1] and cryptand [2.2]; bicyclic polyetheramines such as cryptand [2.2.1] and cryptand [2.2.2], as well as porphyrin, phthalocyanine, polyethylene glycol, and ethylenediaminetetraacetic acid can be used.

[0087] The separation functional layer of the present disclosure is preferably a layer (preferably a coating layer) formed using a composition containing a water-soluble polymer and at least one amine compound selected from the amine compound represented by the general formula (1), the amine compound represented by the general formula (2), and a polyethyleneamine compound, or a 4-methyl-1-pentene polymer, and more preferably a layer formed using a composition containing polyvinyl alcohol and at least one amine compound selected from the amine compound represented by the general formula (1), the amine compound represented by the general formula (2), and a polyethyleneamine compound.

[0088] ~Method of forming separation functional layer~ Next, a method for forming the separation functional layer in the present disclosure will be described. (Formation method 1) Method using polyvinyl alcohol and an amine compound (Formation method 2) Method using 4-methyl-1-pentene polymer

[0089] In the method 1 for forming a separation functional layer in the present disclosure, polyvinyl alcohol and an amine compound are mixed in a dissolved state and dried to form a film.

[0090] A solvent can be used when dissolving the amine compound and polyvinyl alcohol. The solvent is not particularly limited as long as it can dissolve the amine compound and polyvinyl alcohol. From the viewpoint of solubility, examples of the solvent include water, methanol, ethanol, propanol, acetone, dimethylacetamide, and tetrahydrofuran. The solvent may be used alone or in combination of two or more.

[0091] The method of mixing in a dissolved state is not particularly limited, and known methods can be used. For example, stirring with a stirring blade, stirring with a stirrer and stirring bar, stirring with a boiler, stirring with ultrasonic waves (homogenizer), etc. As for the stirring conditions, for example, when stirring with a stirring blade, the rotation speed of the stirring blade is preferably in the range of 1 rpm to 1000 rpm, more preferably in the range of 10 rpm to 400 rpm.

[0092] The order of mixing is not particularly limited, but for example, it is preferable to thoroughly dissolve polyvinyl alcohol in a solvent, and then add and mix the amine compound. If polyvinyl alcohol is mixed with the amine compound in a state where it is not sufficiently dissolved, coarse particles are formed, which may impair uniformity during film formation.

[0093] The method for forming a dry film is not particularly limited, and examples thereof include a method in which an amine compound and polyvinyl alcohol are mixed in a dissolved state to prepare a dissolved mixture (coating liquid), the coating liquid is applied to form a film, and then the film is dried in the air or in a non-oxidizing atmosphere.

[0094] The coating can be performed by a known method, and is not particularly limited. Examples of the coating method include a casting method, a dipping method, a screen printing method, a spray coating method, and a spin coating method.

[0095] The coating amount may be appropriately adjusted depending on the desired thickness of the separation functional layer, and is preferably an amount that results in a thickness of the separation functional layer after drying of 0.01 μm to 1000 μm, and more preferably an amount that results in a thickness of 0.1 μm to 100 μm.

[0096] Drying may be performed in air or in a non-oxidizing atmosphere, for example, in a helium, argon, nitrogen, or other atmosphere.

[0097] In method 2 for forming a separation functional layer in the present disclosure, a 4-methyl-1-pentene polymer is blended with additives (e.g., a heat stabilizer) as necessary, granulated and pelletized in an extruder, and then melt-kneaded in an extruder to form a sheet or film.

[0098] -Support- The composite of the present disclosure includes a support. The support includes a meltblown nonwoven fabric (hereinafter, also simply referred to as "nonwoven fabric") made of fibers having an average fiber diameter of less than 1.5 μm. By including a meltblown nonwoven fabric, in particular, as the support, it is possible to improve both the permeation rate and selectivity of carbon dioxide.

[0099] The nonwoven fabric is obtained by melting a resin composition containing a resin and fiberizing it. A meltblown nonwoven fabric is obtained, for example, by discharging a molten resin composition (e.g., a composition containing a thermoplastic resin) from a nozzle, blowing gas onto the resin composition to fiberize it, and collecting the fiber.

[0100] The resin used for the nonwoven fabric is not particularly limited, and any known thermoplastic resin can be used. Specific examples of thermoplastic resins include polyolefin polymers, which are homopolymers or copolymers of α-olefins such as ethylene, propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene.

[0101] Specific examples of olefin polymers include ethylene homopolymers such as high-pressure low-density polyethylene, linear low-density polyethylene (LLDPE), and high-density polyethylene; ethylene polymers such as ethylene-propylene random copolymers and ethylene-1-butene random copolymers; propylene homopolymers (polypropylene); propylene polymers such as propylene-ethylene random copolymers, propylene-ethylene-1-butene random copolymers (random polypropylene), propylene block copolymers, and propylene-1-butene random copolymers; 1-butene polymers such as 1-butene homopolymers, 1-butene-ethylene copolymers, and 1-butene-propylene copolymers; and 4-methyl-1-pentene polymers such as poly4-methyl-1-pentene homopolymers, 4-methyl-1-pentene-propylene copolymers, and 4-methyl-1-pentene-α-olefin copolymers.

[0102] In addition to the above-mentioned polyolefin polymers, examples of the thermoplastic resin include polyesters (e.g., polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyamides (e.g., nylon-6, nylon-66, polymetaxylene adipamide, etc.), polyvinyl chloride, polyimide, ethylene-vinyl acetate copolymers, polyacrylonitrile, polycarbonate, polystyrene, ionomers, and mixtures thereof.

[0103] Among thermoplastic resins, polyolefin-based polymers are preferred from the viewpoints of excellent spinnability, mechanical strength, chemical resistance, etc. Furthermore, among polyolefin-based polymers, propylene-based polymers are more preferred from the viewpoint of obtaining a nonwoven fabric having a specific fiber diameter range that contributes to the carbon dioxide permeation rate and selectivity. Among propylene-based polymers, propylene homopolymers or propylene-α-olefin copolymers are more preferred, and propylene homopolymers are particularly preferred.

[0104] As the propylene polymer, for example, a propylene homopolymer having a melting point (Tm) of 155°C or higher, preferably in the range of 157°C to 165°C, or a copolymer of propylene and one or more α-olefins having 2 or more carbon atoms (preferably 2 to 8 carbon atoms, excluding 3 carbon atoms) (e.g., ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-pentene, etc.) is preferred.

[0105] As long as the propylene polymer can be melt spun, the melt flow rate (MFR: ASTM D-1238, 230°C, load 2160 g) is preferably 10 g / 10 min to 1000 g / 10 min, more preferably 5 g / 10 min to 500 g / 10 min, and further preferably 100 g / 10 min to 2000 g / 10 min.

[0106] The nonwoven fabric may contain various known additives, such as antioxidants, weather resistance stabilizers, light resistance stabilizers, antiblocking agents, lubricants, pigments, softeners, hydrophilic agents, assistant agents, water repellents, fillers, and antibacterial agents, as long as the additives do not impair the objectives of the present disclosure.

[0107] The nonwoven fabric may be made of only fibers formed by the meltblown method, or may contain other fibers. The other fibers may be short fibers or long fibers. The other fibers may be crimped or non-crinkled fibers. The other fibers may be added for any purpose, such as imparting mechanical properties such as strength, imparting chemical properties, or increasing the amount.

[0108] Examples of the other fibers include short fibers made of polyester such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc. The content of the other fibers is, for example, preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the total mass of the nonwoven fabric.

[0109] The average fiber diameter of the fibers in the meltblown nonwoven fabric of the present disclosure is less than 1.5 μm. When the average fiber diameter is less than 1.5 μm, it is possible to improve both the carbon dioxide permeation rate and the carbon dioxide selectivity while maintaining good strength of the composite. Among these, for the same reasons as above, 1.3 μm or less is preferable, 1.2 μm or less is more preferable, and 1.0 μm or less is even more preferable. The lower limit of the average fiber diameter of the fibers may be, for example, 0.3 μm. When the average fiber diameter is 0.3 μm or more, the strength as a support can be well maintained. From the viewpoint of well maintaining the strength of the composite and further improving both the carbon dioxide permeation rate and selectivity, the average fiber diameter of the fibers is preferably in the range of 0.3 μm to 1.2 μm, and more preferably in the range of 0.5 μm to 1.2 μm. The average fiber diameter is measured by randomly selecting 100 fibers from an electron microscope photograph (magnification 3000x) of the nonwoven fabric, measuring the diameter of the selected fibers, and calculating the average of the measured values.

[0110] Next, the physical properties of the nonwoven fabric will be described. The average pore size of the nonwoven fabric is 15g / m 2 When measured by the method described above, the average pore size is preferably less than 6.0 μm, more preferably 0.5 μm to 5.8 μm, further preferably 2.0 to 5.8 μm, and particularly preferably 3.0 to 5.0 μm. By having the average pore size within the above range, both the permeation rate and selectivity of carbon dioxide can be improved. The average pore size of a nonwoven fabric is determined by soaking a test piece of the nonwoven fabric in a fluorine-based inert liquid and measuring the average pore size using a capillary flow porometer (e.g., Model CFP-1200AE manufactured by Porous Materials, Inc.).

[0111] The basis weight of the nonwoven fabric is not particularly limited, and is, for example, 5 g / m 2 ~200g / m 2 and 10 g / m 2 ~150g / m 2 is preferred, and 10 g / m 2 ~50g / m 2 When the basis weight is within the above range, both the carbon dioxide permeation rate and selectivity can be improved. The method for measuring the basis weight in the present disclosure is as described in the Examples below.

[0112] The layer thickness of the nonwoven fabric is not particularly limited, and is preferably from 20 μm to 1000 μm, more preferably from 40 μm to 500 μm, further preferably from 100 μm to 200 μm, and particularly preferably from 100 μm to 150 μm. The layer thickness of the nonwoven fabric of the present disclosure can be measured by measuring any 10 points with a digital thickness meter conforming to JIS Z1702 and calculating the average of the measured values.

[0113] The porosity of the nonwoven fabric is not particularly limited, and may be, for example, 95% or less. From the viewpoint of improving both the permeation rate and selectivity of carbon dioxide, the porosity is preferably 65% ​​or more, more preferably 70% or more, even more preferably 75% or more, and particularly preferably 80% or more. The preferred porosity is 80% to 95%. The void ratio is calculated using the filling rate (%) calculated using the following formula (1) according to formula (2). Filling rate = (weight (g / m 2 ) / Thickness (μm) / Resin Density (g / cm 3 ))×100 (1) Porosity (%)=100-Filling rate (%) ···(2)

[0114] The meltblown nonwoven fabric can be obtained by a known meltblown nonwoven fabric manufacturing method, for example, by melting the raw material polypropylene, discharging it from a spinning nozzle, exposing it to high-temperature, high-pressure gas to form fine fibers, and collecting and depositing the polypropylene fine fibers on a collector such as a perforated belt or perforated drum. The production conditions are as follows: the average fiber diameter of the polypropylene fine fibers is less than 1.5 μm (preferably 0.3 μm to 1.2 μm) (to a desired thickness as necessary); for example, the velocity (discharge volume) of the high-temperature, high-pressure gas is set to 4 Nm 3 / min / m~30Nm 3 / min / m, the distance from the outlet of the spinning nozzle to the collection surface (e.g., a porous belt) is 3 cm to 55 cm, and the mesh width of the collector (e.g., a porous belt) is 5 mesh to 200 mesh, etc., may be appropriately selected.

[0115] The nonwoven fabric manufacturing apparatus using the meltblown method is not particularly limited, and a general meltblown apparatus can be applied. In addition, the conditions for carrying out the meltblown method (for example, the temperature of the spinneret, the melting temperature of the thermoplastic resin, the temperature of the heating gas, etc.) are not particularly limited as long as the fibers (fibrous resin) having the above-mentioned average fiber diameter can be produced. The average fiber diameter can be adjusted by appropriately changing the size of the spinneret outlet, the temperature of the spinneret, the melting temperature, the temperature and flow rate of the heating gas, etc.

[0116] [Other layers] The composite of the present disclosure may further include layers other than the separation functional layer. Examples of other layers include a carrier elution prevention layer and a water permeation inhibition layer that are provided on the surface of the separation functional layer opposite to the surface where the separation functional layer is adhered to the support.

[0117] In the method for producing the composite of the present disclosure, the separation functional layer and the support may be formed separately and then bonded together, or the support may be formed on the separation functional layer. Methods for bonding the separation functional layer and the support include, for example, pressure bonding, heat fusion, adhesives, and pressure sensitive adhesives. EXAMPLES

[0118] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. In addition, unless otherwise specified, "parts" are based on mass.

[0119] Example 1 [Preparation of separation functional layer] 2 g of polyvinyl alcohol (weight average molecular weight: 66000, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a water-soluble polymer was dissolved in 198 g of water, and 2 g of N-(2-aminoethyl)ethanolamine (manufactured by Tokyo Chemical Industry Co., Ltd.) as an amine compound was added to prepare a mixed solution. The resulting mixed solution was then spread in a petri dish and dried at room temperature in the air for 12 hours or more to obtain a polymer membrane 1. The content of N-(2-aminoethyl)ethanolamine in the resulting polymer membrane 1 was 50 mass %, and the membrane thickness was 8.8 μm.

[0120] [Preparation of support] Using a meltblown nonwoven fabric manufacturing device, propylene homopolymer (MFR (based on ASTM D1238, 260°C, 5 kg load; the same applies below): 25 g / 10 min) was fed into the die, and heated air (300°C, 770 Nm) was blown from both sides of the nozzle at a discharge rate of 0.08 g / min per nozzle hole from the die set at a temperature of 300°C. 3 / hr / m) and molten propylene homopolymer was discharged and sprayed onto a collector at a DCD (distance from the surface of the spinneret to the collector) of 150 mm, resulting in a basis weight of 15 g / m 2 A meltblown nonwoven fabric 1 was obtained.

[0121] [Preparation of the complex] A polymer film 1 was adhered onto a meltblown nonwoven fabric 1 to obtain a composite 1.

[0122] Example 2 [Preparation of separation functional layer] Polymer membrane 2 having a different thickness from polymer membrane 1 was obtained by the same method as in Example 1. The content of N-(2-aminoethyl)ethanolamine in the obtained polymer membrane 2 was 50 mass %, and the membrane thickness was 10.1 μm. [Preparation of support] Using a meltblown nonwoven fabric manufacturing device, propylene homopolymer (MFR: 25 g / 10 min) was fed into the die, and heated air (300°C, 700 Nm) was blown from both sides of the nozzle at a discharge rate of 0.10 g / min per nozzle hole from the die set at a temperature of 300°C. 3 / hr / m) and the molten propylene homopolymer was discharged and sprayed onto a collector with a DCD of 150 mm to obtain a basis weight of 15 g / m 2 As a result, a meltblown nonwoven fabric 2 was obtained. [Preparation of the complex] A polymer film 2 was adhered onto the meltblown nonwoven fabric 2 to obtain a composite 2.

[0123] Example 3 [Preparation of separation functional layer] A polymer membrane 1 was obtained in the same manner as in Example 1. [Preparation of support] Using a meltblown nonwoven fabric manufacturing device, propylene homopolymer (MFR: 25 g / 10 min) was fed into the die, and heated air (300°C, 700 Nm) was blown from both sides of the nozzle at a discharge rate of 0.10 g / min per nozzle hole from the die set at a temperature of 300°C. 3 / hr / m) and the molten propylene homopolymer was discharged and sprayed onto a collector with a DCD of 150 mm to obtain a basis weight of 15 g / m 2 A meltblown nonwoven fabric 3 was obtained. [Preparation of the complex] A polymer film 1 was adhered onto a meltblown nonwoven fabric 3 to obtain a composite 3.

[0124] Example 4 [Preparation of separation functional layer] Forrap (product name: manufactured by Riken Fabro Corporation, main component: poly-4-methyl-1-pentene (PMP), melting point of main component of product raw material: 224° C., product heat resistance temperature: 180° C.) was prepared as polymer film 3. The film thickness was 12.9 μm. [Preparation of support] A meltblown nonwoven fabric 2 was obtained in the same manner as in Example 2. [Preparation of the complex] A polymer film 6 was adhered onto the meltblown nonwoven fabric 2 to obtain a composite 4 .

[0125] Comparative Example 1 [Preparation of separation functional layer] Polymer membrane 4 having a different thickness from polymer membrane 1 was obtained by the same method as in Example 1. The content of N-(2-aminoethyl)ethanolamine in the obtained polymer membrane 4 was 50 mass %, and the membrane thickness was 11.7 μm. [Preparation of support] As a support, a PVDF filter (containing polyvinylidene fluoride; Durapore (registered trademark), filter aperture size: 0.45 μm, product code: HVLP02500, manufactured by Merck Millipore) was prepared (hereinafter referred to as "Filter 1"). [Preparation of the complex] A polymer membrane 4 was adhered onto the filter 1 to obtain a comparative composite 1.

[0126] Comparative Example 2 [Preparation of separation functional layer] Polymer membrane 5 having a different thickness from polymer membrane 1 was obtained by the same method as in Example 1. The content of N-(2-aminoethyl)ethanolamine in the obtained polymer membrane 5 was 50 mass %, and the membrane thickness was 9.4 μm. [Preparation of support] Using a meltblown nonwoven fabric manufacturing device, propylene homopolymer (MFR: 25 g / 10 min) was fed into the die, and heated air (300°C, 700 Nm) was blown from both sides of the nozzle at a discharge rate of 0.15 g / min per nozzle hole from the die set at a temperature of 300°C. 3 / hr / m) and the molten propylene homopolymer was discharged and sprayed onto a collector with a DCD of 350 mm to obtain a basis weight of 15 g / m 2 A meltblown nonwoven fabric 4 was obtained. [Preparation of the complex] A polymer film 5 was adhered onto the meltblown nonwoven fabric 4 to obtain a comparative composite 2.

[0127] Comparative Example 3 [Preparation of separation functional layer] As in Example 4, a polymer membrane (FOR-WRAP) 3 was prepared. [Preparation of support] Similar to Comparative Example 1, Filter 1 was prepared. [Preparation of the complex] A polymer membrane 3 was adhered onto the filter 1 to obtain a comparative composite 3.

[0128] (Measurement evaluation) [Measuring the thickness of the separation functional layer] The thickness of the separation functional layer was measured at five arbitrary points on each layer using a micrometer (MDH-25MB manufactured by Mitutoyo Corporation) and the average value was calculated. The results are shown in Tables 1 and 2.

[0129] [Measurement of the average fiber diameter of the support] The support was photographed at a magnification of 3000 times using an electron microscope (Hitachi S-3500N). 100 fibers were randomly selected from the micrograph, and the width (diameter) of each fiber was measured, and the average of the measured values ​​was calculated to obtain the average fiber diameter. The results are shown in Tables 1 and 2.

[0130] [Measurement of the weight of the support] A 100mm x 100mm sample was taken from the support and its weight was measured. 2 The results are shown in Tables 1 and 2.

[0131] [Measurement of support thickness] The sample used for the basis weight measurement was measured at 10 random locations using a digital thickness gauge according to JIS Z 1702-1994, and the average of the measured values ​​was calculated to be the thickness of the support. The results are shown in Tables 1 and 2.

[0132] [Measurement of porosity of support] The porosity of the support (voids per unit volume) was calculated from the following formula (1). In formula (1), the packing rate of the support (%; equivalent to the amount of resin per unit volume) was calculated from the following formula (2). The results are shown in Tables 1 and 2. Porosity (%)=100-Filling rate (%) ···(1) Filling rate = (weight (g / m 2 ) / Thickness (μm) / Resin Density (g / cm 3 ))×100 (2) The resin densities are as follows: Polypropylene polymer: 0.91g / cm 3 Polyvinylidene fluoride (PVDF): 1.78g / cm 3

[0133] [Measurement of the average pore size of the support] The support was immersed in a fluorine-based inert liquid (3M, trade name: Fluorinert), and the average pore size (μm) was measured using a capillary flow porometer (Model CFP-1200AE, Porous Materials, Inc.). The measurements were carried out in a temperature-controlled room at a temperature of 20±2°C and a humidity of 65±2%, as specified in JIS Z 8703-1983 (standard conditions for testing). The results are shown in Tables 1 and 2.

[0134] [Gas separation test of carbon dioxide and coexisting gases 1] The selectivity and permeation flux of carbon dioxide were evaluated using the composites of Examples 1 to 4 and the comparative composites of Comparative Examples 1 to 3. Nitrogen gas was used as the coexisting gas.

[0135] A schematic diagram of the apparatus is shown in Figure 1. A mixed gas (10% by volume of carbon dioxide gas and 90% by volume of coexisting gas (nitrogen gas)) was supplied to one side of the composites of Examples 1 to 4 and Comparative Examples 1 to 3, and the permeation flux of the gas that permeated to the other side (permeation rate Q CO2 and nitrogen gas permeation rate Q N2 ;Unit: GPU=1.0×10 -6 cm 3 (STP) / (s cm 2 The permeation flux was measured using gas chromatography and a flow meter under the following conditions, and the permeation flow rate Q N2 Permeation flow rate Q CO2 The carbon dioxide selectivity coefficient α (CO2 / N2), expressed as the ratio of

[0136]

number

[0137] In the above formula, Q i is the permeation flux of each gas, n i is the volume of each gas (cm 3 ), A is the membrane area (cm 2 ), t is time (sec), Δp i means the pressure difference (cmHg) between the partial pressure on the supply side and the partial pressure on the permeate side of each gas. Note that i represents each gas.

[0138]

number

[0139] In the above formula, α is the carbon dioxide selectivity coefficient, Q CO2 is the carbon dioxide permeation flux, Q N2 means the permeation flux of nitrogen gas, which is a coexisting gas.

[0140] [Gas permeability measurement device setting conditions 1] Gas supply: approx. 100mL / min Measurement temperature: 40℃ Supply gas composition: carbon dioxide / nitrogen = 10 / 90 (vol% / vol%) Permeate side sweep gas: He Permeation side sweep gas flow rate: Approximately 50 mL / min Relative humidity: 90% Carbon dioxide differential pressure (carbon dioxide pressure on the supply side - carbon dioxide pressure on the permeation side): Approximately 10 kPa

[0141] [Gas chromatography analysis conditions 1] TCD detector: GC2014AT (Shimadzu Corporation) Column: PorapakQ 80 / 100

[0142] [Table 1]

[0143] As is clear from Table 1, in Examples 1 to 3 in which a meltblown nonwoven fabric having an average fiber diameter of less than 1.5 μm was used as the support for forming the composite, the carbon dioxide selectivity coefficient and the carbon dioxide permeation flux were excellent. For example, the composite 1 shown in Example 1 exhibited a carbon dioxide selectivity coefficient of 280 and a carbon dioxide permeation flux of 36. In contrast, as shown in Comparative Example 1 in Table 1, the comparative composite 1 had a carbon dioxide selectivity coefficient of 215 and a carbon dioxide permeation flux of 34, and both the carbon dioxide selectivity coefficient and the carbon dioxide permeation flux were inferior. In addition, as shown in Comparative Example 2, the comparative composite 2 used a meltblown nonwoven fabric 4 having an average fiber diameter of 1.5 μm as the support, and as a result, the carbon dioxide selectivity coefficient was 211 and the carbon dioxide permeation flux was 35, and both the carbon dioxide selectivity coefficient and the carbon dioxide permeation flux were inferior to those of the composites shown in Examples 1 to 3.

[0144] [Gas separation test of carbon dioxide and coexisting gases 2] The composite of Example 4 and the comparative composite of Comparative Example 3 were used to evaluate the selectivity and permeation flux of carbon dioxide. For the measurements, the same equipment as in Gas Separation Test 1 using a mixed gas of carbon dioxide and nitrogen gas was used. The results are shown in Table 2.

[0145] [Gas permeability measurement device setting conditions 2] Gas supply: approx. 50mL / min Measurement temperature: 40℃ Supply gas composition: carbon dioxide / nitrogen gas = 10 / 90 (vol% / vol%) Permeate side sweep gas: He Permeation side sweep gas flow rate: Approximately 50 mL / min Relative humidity: 0% Carbon dioxide differential pressure (carbon dioxide pressure on the supply side - carbon dioxide pressure on the permeation side): Approximately 10 kPa

[0146] [Gas chromatography analysis conditions 2] TCD detector: GC2014AT (Shimadzu Corporation) Column: PorapakQ 80 / 100

[0147] [Table 2]

[0148] As is clear from Table 2, a meltblown nonwoven fabric 2 having an average fiber diameter of less than 1.5 μm was used as the support for forming the composite, and composite 4, in which a polymer membrane 3 (separation functional layer) different from those in Examples 1 to 3 was provided using this meltblown nonwoven fabric 2 as the support, had superior carbon dioxide selectivity coefficient and carbon dioxide permeation flux compared to comparative composite 3, which used a PVDF filter (filter 1) as the support. [Industrial Applicability]

[0149] The composite for carbon dioxide separation according to the present disclosure maintains the carbon dioxide permeation rate and has excellent carbon dioxide selectivity, and therefore can be suitably used in membrane separation methods. [Explanation of symbols]

[0150] 1 Gas cylinder 2. Compatible gas cylinders 3. He gas cylinder 4...Flow rate controller 5...humidifier 6. Pressure gauge 7...Dew point meter 8. Membrane cell 9... Constant temperature bath 10. Dehumidification trap 11. Automatic gas sampler 12. Gas chromatography

Claims

1. A carbon dioxide separation functional layer and a support, The support comprises a meltblown nonwoven fabric made of fibers having an average fiber diameter of less than 1.5 μm.

2. 2. The composite for carbon dioxide separation according to claim 1, wherein the average fiber diameter of the fibers is 0.3 μm to 1.2 μm.

3. The composite for carbon dioxide separation according to claim 1 or 2, wherein the meltblown nonwoven fabric has an average pore size of less than 6.0 μm.

4. 3. The composite for carbon dioxide separation according to claim 1, wherein the fiber is made of a resin composition containing a propylene homopolymer.

5. The carbon dioxide separation composite according to claim 1 or 2, wherein the carbon dioxide separation functional layer satisfies either the following (A) or (B): (A) A water-soluble polymer and at least one amine compound selected from the group consisting of an amine compound represented by the following formula (1), an amine compound represented by the following formula (2), and a polyethylene polyamine compound. (B) 4-methyl-1-pentene polymer 【Chemistry 1】 [In formula (1), R 1 , R 3 and R 3 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a hydroxyethyl group. 【Chemistry 2】 [In formula (2), R 1 , R 3 and R 3 each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

6. The carbon dioxide separation composite according to claim 5 , wherein the carbon dioxide separation functional layer satisfies the following (A): (A) comprises a water-soluble polymer made of polyvinyl alcohol, and at least one amine compound selected from the group consisting of the amine compound represented by the formula (1), the amine compound represented by the formula (2), and a polyethylene polyamine compound.

7. 6. The composite for carbon dioxide separation according to claim 5, wherein the water-soluble polymer has a weight average molecular weight of 2,000 to 1,000,000.

Citation Information

Patent Citations

  • Carbon dioxide separation membrane, support for carbon dioxide separation membrane, and method of manufacturing them

    JP2013027806A

  • Polymer membrane and method for producing the same, and method for separating carbon dioxide

    JP2018144022A